Gas bubble size estimation in peat soils from EM wave scattering observed with ground penetrating radar. Issue 4 (6th April 2017) - Terry, Neil; Slater, Lee
Abstract: The size of biogenic gas bubbles in peatlands is believed to regulate ebullition of carbon gases to the atmosphere. The measurement of electromagnetic (EM) wave travel times using ground penetrating radar (GPR) is a proven field‐scale method for indirect estimation of volumetric gas content. However, there is also the possibility that information on the size of the gas bubbles can be determined from the analysis of the spectral content of GPR signals as scattering attenuation possesses a frequency dependence for bubbles smaller than the EM wavelength (Rayleigh‐type scattering). Theoretical modeling shows that GPR data acquired with typical antenna frequencies are likely to be affected by bubble size in peat soils. Analysis of GPR data from two recent studies on peat monoliths where biogenic gas production was documented produced results consistent with the model predictions. Using the approach, zero offset cross‐borehole GPR data in a northern peatland suggest that large bubble clusters (i.e., 0.05 m radius) occur in peat. These findings broaden the utility of GPR for providing information on biogenic gas dynamics in peatlands. Key Points: GPR frequency data can help to estimate bubble size in peat A quantitative bubble size model is derived Results indicate maximum 0.05 m and mean 0.011 m radius bubbles from a field site